Cognitive Efficiency of Slovenian, Indian and Gambian Gifted Students in Performing Mental Tasks - Kukanja Gabrijelčič, Mojca; Šavs, Ema; Nemec, Teja (Revija za elementarno izobraževanje, 2023)
In this paper, we present a comparative analysis between registered gifted Slovenian, Gambian, and Indian students in which we sought to find out how they perform in solving selected mental tasks, where we were focused on logical-mathematical and spatial intelligence as a function of the social environment from which the students came. We found that the results for the test groups differed. Out of ten task sets, Slovenian students performed better than their Indian and Gambian peers in as many as seven task sets; in four tasks we found a statistically significant difference between Slovenian and Indian children, and a comparison between Slovenian and Gambian students shows that Slovenian children scored better on mental task sets in all groups.
Keywords: intelligence, giftedness, gifted students, mental tasks, cultural environment, education in India, education in Gambia.